2005
DOI: 10.1243/095440505x32634
|View full text |Cite
|
Sign up to set email alerts
|

Application of singular spectrum analysis to tool wear detection using sound signals

Abstract: The aim of the present work is to study the applicability of singular spectrum analysis (SSA) to the processing of the sound signal from the cutting zone during a turning process, in order to extract information correlated with the state of the tool. SSA is a novel non-parametric technique of time series analysis that decomposes a given time series into an additive set of independent time series. The correspondence between the singular spectrum obtained using SSA and the frequency spectrum of the signal is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…4. Many of the previous studies in this area use the sound signals present in the frequency range above machine background noise to develop the tool wear monitoring system [6][7][8][9][10][11][12][13][14][15]. However, as there is little reporting of using spindle noise in tool wear monitoring, this present work concentrates on the spindle noise signal as a signal of interest to extract a promising feature for tool condition monitoring.…”
Section: Observation Of the Sound From A Cutting Cyclementioning
confidence: 99%
See 2 more Smart Citations
“…4. Many of the previous studies in this area use the sound signals present in the frequency range above machine background noise to develop the tool wear monitoring system [6][7][8][9][10][11][12][13][14][15]. However, as there is little reporting of using spindle noise in tool wear monitoring, this present work concentrates on the spindle noise signal as a signal of interest to extract a promising feature for tool condition monitoring.…”
Section: Observation Of the Sound From A Cutting Cyclementioning
confidence: 99%
“…This processing technique was used to extract the sound features from the cutting zone during the turning process. The results showed that the extracted features from sound and feed motor current signals correlate with tool wear state [14]. Raja used sound signal analysis, using the Hilbert-Huang Transform (HHT), to monitor flank wear [8,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The acquisition of process variable values like power used for cutting, amount of heat vibration, current for spindle motor current, surface roughness and their correlation to the tool wear were considered to monitor the tool wear indirectly considered. Researches like Alonso et.al [1] suggested a mechanism to predict the degrees of tool flank wear by artificial neural network that works on the sound signals emitted at the time of conversion procedure by considering feed cutting force. Sadettin et.al [2] establish the vibration of amplitude is straightforwardly to the intensification tool wear.…”
Section: Introductionmentioning
confidence: 99%
“…asperity height, size and distributions. Salgado and Alonso [11,12] presented a tool condition monitoring system (TCMS) for on-line tool wear monitoring using the feed motor current and the sound signal. The results showed that the proposed TCMS is fast and reliable for tool condition monitoring.…”
Section: Introductionmentioning
confidence: 99%